A 'special relationship' in higher education? What influence might the US higher education sector have in terms of support for international students in the UK?. (2nd July 2016) - Lochtie, David John
Abstract : As international student migration and comparative education research have increased worldwide, greater interdependency between national Higher Education (HE) systems has developed with policy and practice frequently being shared internationally. As a key player in the international student market the United States of America is especially influential over its peers and competitors, including the UK. The market of HE with rising, and variable, tuition fees which has existed in the USA for some time bears a resemblance to recent developments and proposals in the UK. Furthermore there are clear parallels between long standing federal funded access initiatives in the USA and recent UK governments' widening participation policies. This paper examines whether international student support in institutions across the globe may be influenced similarly by activities in the USA, specifically looking at academic advising and the potential of utilising professional academic advisors to support personal tutoring in the UK.